2023
DOI: 10.4149/gpb_2021009
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite motif containing 28 (TRIM28) promotes the growth and migration of endometrial carcinoma cells by regulating the  AKT/mTOR signaling pathway

Abstract: Although the medical science has been developed for decades, the molecular mechanism of endometrial cancer (EC) is not yet completely clear. Previous studies have shown that the tripartite motif containing 28 (TRIM28) plays a crucial role in tumor development. However, TRIM28 is rarely studied in EC, and its role and mechanism need to be further determined. This study was aimed to delve into the related molecular mechanism underling the role of TRIM28 in EC cell growth and migration. qPCR assays and Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…These cell proliferation could be abrogated by the specific mTOR inhibitor everolimus ( 24 ). Similarly, TRIM28 can promote endometrial cancer cell growth and migration by activating AKT/mTOR signaling pathway ( 25 ). TRIM28 can also play a role in tumor cell proliferation as a direct target of microRNAs.…”
Section: Role Of Trim28 In the Cancer Cell Cycle And Proliferationmentioning
confidence: 99%
“…These cell proliferation could be abrogated by the specific mTOR inhibitor everolimus ( 24 ). Similarly, TRIM28 can promote endometrial cancer cell growth and migration by activating AKT/mTOR signaling pathway ( 25 ). TRIM28 can also play a role in tumor cell proliferation as a direct target of microRNAs.…”
Section: Role Of Trim28 In the Cancer Cell Cycle And Proliferationmentioning
confidence: 99%
“…VCAM1 [1413], PTPRD (protein tyrosine phosphatase receptor type D) [1426] and hsa-mir-17-5p [1689] are associated with prognosis in patients with gestational diabetes mellitus. IGF2BP1 [453], DAPK1 [183], PTPRD (protein tyrosine phosphatase receptor type D) [412], TCF3 [1690], SMARCA4 [1691] and TRIM28 [1692] biomarkers are vital for endometrial cancer. Research have shown that PTPRD (protein tyrosine phosphatase receptor type D) [656], PDGFB (platelet derived growth factor subunit B) [642], DAPK1 [751], hsa-mir-4432 [1693], SMARCA4 [1694] and TRIM28 [1695] participates in hypertension.…”
Section: Discussionmentioning
confidence: 99%